EFEK GENETIK IRADIASI SINAR GAMMA PADA LALAT BUAH (Drosophila melanogaster Meig) JANTAN PRA KAWIN - Rochestri Sofyan; Yana Sumpena; Supartini Syarif; Ira Adiyati R (Research Center for Biology-Indonesian Institute of Sciences, 2007)
An investigation about the effect of gamma irradiation on the progeny development of male fruit fly (Drosophila melanogaster Meig) pre-marital has been done.The purpose of this study is to comprehend the changes in progeny as well as the probability of abnormal phenotype to fruit fly progeny as the result of gamma irradiation to male fruit fly pre-marital.The study has been conducted using Completely Randomize Design method with six repetitions. Pre-marital male fruit flies were irradiated at the doses of 10, 15 and 20 Gy with gamma ray from